Prevalence And Allele Frequency Of Colour Blindness In Al-Najaf Al Ashraf Province - W. Alkhalaf , Ameer; S. Al-khafaji, Rafie (Medical Science Journal for Advance Research, 2022)
Background: Colour blindness or colour vision deficiency is an inability or reduced ability to described certain colours, there are several types of colour blindness but the more common type red-green colour blindness that inherited x-linked disorder, hence it was more distribution in males (hemizygote) but it was less prevalent in females because she had two x chromosomes, she may be affected or a carrier to disorder. We examined 2470 participant (2158 male and 312 female) by using Ishihara plate (24 plates edited). This study conducted to find out the prevalence of colour blindness in Al-Najaf province. In the present study, Among those was screened for colour deficiency, 107 of them(4.33%)were diagnosed with colour blindness, the rate was a difference among gender 105(4.87 %) in male and it was 2(0.64) % in female. The deuteranomaly was the highest type 38(35.51%) then deuteranopia was 31(28.97 %), the protanomaly was 23(21.50%), the protanopia was 10(9.35%), At last, the achromacy was lowest 5(4.67 %) among infected colour blindness. The deutan :protan ratio was 2.03:1. This rate (in our study) was approximately similar to the rate recorded in Al-Qadisiyah University (5.2 % in male and 0.4% in female) and less the rate in the centre and north Iraq (Baghdad, Duhok and Erbil province).